The VTC-taxi relationship and the autonomous concepts of European Law - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Spanish legislation regarding taxis and VTC services has traditionally contained numerous restrictions on access to and exercise of the activity. The judgment of the Court of Justice of the European Union of 8 June 2023 in the Prestige & Limousine and AMB case repeals the possibility of making VTC licences conditional on the number of taxi licences granted. Surprisingly, this and other restrictions continue to be upheld by the Spanish courts and the legislator introduces new restrictive measures in favour of taxi services and to the clear detriment of other private transport companies, after that judgment. An analysis of the European concepts of EU law on free access to and exercise of economic activities calls for a change in the case law on this matter in the Spanish courts in general and in the Supreme Court in particular.